Romania : Financial Sector Assessment Program-Technical Note on Calibration of a Debt-Service-to-Income Limit in Romania-Evidence from Microdata. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2018)
This Technical Note discusses calibration of a debt-service-to-income (DSTI) limit in Romania. The recent pick-up in household credit in Romania has given rise to a need for revisiting the design of existing macroprudential tools addressing household vulnerabilities. The National Bank of Romania is considering a redesign of its existing macroprudential tool related to household indebtedness, including expanding its scope to cover all household loans. The analysis of loan-level data from the Central Credit Register suggests that the probability of default of a borrower is highly sensitive to any changes in DSTI at DSTI ratios at about 50 percent, particularly for mortgage loans. It is recommended to set the limit such that loans do not exceed this sensitivity threshold.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet